Design and Development of Underwater ROV for Dam Inspection - Elangovan, Muniyandy; Siddarth , B Yuvan; Uduupa, R Govindram; Babu , M Mohan (PREPARE@u® | IEI Conferences, 2021)
India is a developing country that relies heavily on agriculture. A large number of dams have been built to store water and use it when it is required for agriculture. Physical inspection is currently performed outside of the dam, but it is not done efficiently inside the dam due to a lack of technology to reach the bottom of the dam and the wall inside the water. Keeping those criteria in mind, this project has created a vehicle (robot) that can dive into the dam water and take video and possibly photographs to verify the consistency of the wall’s condition. This system includes a camera for capturing damage and estimating the need for wall reinforcement. It helps to identify the weaker or damaged part of the dam wall. Outside the Dam, a monitoring system is installed to collect data from the ROV and determine if additional action is required for additional inspections. Since there isn’t enough light in the deeper parts of the dam, lighting is needed. It is recommended to have a small pump to get the water so that the consistency of the water can be checked at any time. This vehicle can assist the community in maintaining high-quality water in a dam for human consumption while reducing the risk of human injury during an inspection.